The Implementation of Authentic Assessment in Arabic Language Learning at Madrasah Aliyah: A Qualitative Study on Learning Processes and Outcomes - Gepira Enung Nurjanah; Maysi Nabila Syawalni; Wildatun Nihayah (Gunung Djati Conference Series, 2026)
This study aims to describe the implementation of authentic assessment in Arabic language learning at Madrasah Aliyah. The qualitative findings indicate that authentic assessment is carried out through observations, rubrics, projects, and portfolios that evaluate both the learning process and learning outcomes comprehensively. The results show that the implementation of authentic assessment enhances students’ motivation, creativity, and Arabic language proficiency, although challenges remain, including limited time, insufficient facilities, and varying levels of teacher competence. This research employs a descriptive qualitative approach to illustrate how authentic assessment is applied in Arabic language learning at Madrasah Aliyah. Data were collected from teachers, students, and school principals through interviews, observations, and documentation, supported by secondary sources such as lesson plans and portfolios. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, with triangulation used to ensure data validity. The implementation of authentic assessment in Arabic language learning at Madrasah Aliyah is conducted continuously, evaluating both process and product through various instruments such as rubrics, projects, portfolios, and classroom observations. This assessment approach increases students’ motivation, creativity, and sense of responsibility in learning. Despite challenges such as limited time, large class sizes, and inadequate facilities, teachers continue to optimize authentic assessment to create meaningful and contextual learning experiences.